Ghost-haunted land : contemporary art and post-Troubles Northern Ireland - Long, Declan (Manchester University Press, 2017)
Since the signing of the Good Friday Agreement in 1998 - the formal end-point of the thirty-year modern 'Troubles' - contemporary visual artists have offered diverse responses to post-conflict circumstances in Northern Ireland. In Ghost-Haunted Land - the first book-length examination of post-Troubles contemporary art - Declan Long highlights artists who have reflected on the ongoing anxieties of aftermath.